2020
DOI: 10.1002/mabi.202000314
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Anisotropic Human Hair Keratin Scaffolds Fabricated via Directed Ice Templating

Abstract: Human hair keratin (HHK) is successfully exploited as raw materials for 3D scaffolds for soft tissue regeneration owing to its excellent biocompatibility and bioactivity. However, most HHK scaffolds are not able to achieve the anisotropic mechanical properties of soft tissues such as tendons and ligaments due to lack of tunable, well‐defined microstructures. In this study, directed ice templating method is used to fabricate anisotropic HHK scaffolds that are characterized by aligned pores (channels) in between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 50 publications
(62 reference statements)
1
19
0
Order By: Relevance
“…From this knowable, RHK hydrogel is a reversible thixotropic system. Noticeable feature is the absence of distinct phase separation between the keratin hydrogels and the surrounding aqueous medium as the article says (Zhao et al, 2020). We believe that the formation of keratin hydrogels is due to the three-dimensional network structure formed by the binding of keratin molecules, bound water adsorbed by keratin hydrophilic groups, and the unbound water clamped in the pore structure.…”
Section: Rheological Properties Of Rabbit Hair Keratin Hydrogelsmentioning
confidence: 92%
See 1 more Smart Citation
“…From this knowable, RHK hydrogel is a reversible thixotropic system. Noticeable feature is the absence of distinct phase separation between the keratin hydrogels and the surrounding aqueous medium as the article says (Zhao et al, 2020). We believe that the formation of keratin hydrogels is due to the three-dimensional network structure formed by the binding of keratin molecules, bound water adsorbed by keratin hydrophilic groups, and the unbound water clamped in the pore structure.…”
Section: Rheological Properties Of Rabbit Hair Keratin Hydrogelsmentioning
confidence: 92%
“…The solvent crystallizes when the temperature is below freezing point, and the keratin macromolecules combine with each other by disulfide bonds, hydrogen bonds, hydrophobicity, electrostatic attraction, and van der Waals forces (Esparza, 2018b), when the temperature returns to above freezing point, as the solvent crystals melt, solvent and other components are enveloped in a three-dimensional network of keratin, an interconnected microporous hydrogel structure is formed (Lozinsky 2002;Henderson et al, 2013). In a recent study by Chua et al (Cui et al, 2019;Chua et al, 2020;Zhao et al, 2020), HHK sponges was prepared by this method. However, as with previous studies, the main research focuses on the mechanical and biocompatibility of hydrogels, whether pure or hybrid keratin hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…Materials Advances aspect ratio rod-like or fiber-like structures, 114 especially bioderived fibers such as chitin, amyloid fibers, 115 cellulose nanofibers, 48,[116][117][118][119] keratin filaments, 120,121 SiC fibres, 59 platelets, 61,[122][123][124][125][126][127] and nanorods, 128 has been reported. However, there are few investigations that systematically probe the effect of particle shape or colloid aspect ratio on freezinginduced orientational phase transitions.…”
Section: Reviewmentioning
confidence: 99%
“…Human hair keratin presents exciting new possibilities to the field of biomedical science as an abundant, bioactive, affordable, sustainable, and potentially autologous source of human-compatible material [8]. In recent years, hair keratin templates in the forms of coatings [9,10], hydrogels [11], sponges [12][13][14], and fibrous mats [15], have been fabricated and demonstrated to support the natural function of living tissues, both in vitro and in vivo. It has been shown that injectable keratin hydrogels were able to increase survival rates in a large animal lethal hemorrhage model, while also exhibiting increased mean arterial pressure and decreased shock index when compared to both commercial chitosan dressing and cotton gauze [16].…”
Section: Introductionmentioning
confidence: 99%